Evaluation of Vitamin B12 Serum Level in a Group of Jordanian Patients with Type 2 Diabetes Mellitus - Al-Amoush, Adeeb; Shaqra, Qasem Abu; Al-Groom, Rania (Pakistan Journal of Nutrition, 2016)
Diabetes Mellitus is one of the most prevalent metabolic disorders affecting humans and metformin is commonly used in its treatment protocol. However, this hypoglycemic agent is known to cause vitamin B12 deficiency, studies released from Jordan indicated the lack of relationship between both diabetes mellitus or metformin use and vitamin B12 deficiency. This investigation was under taken to further clarify this association among Jordanian patients with type 2 diabetes mellitus. A total number of 110 type 2 diabetes patients were enrolled in this study. The mean age of patients was 56.3 years (SD of 11.02) and female constituted 61% of subjects. The percentage of patients with vitamin B12 deficiency was established at 39.1% and those receiving metformin treatments amounted to 76.4% of the studied population. Duration of diabetes had no effect on vitamin B12 deficiency (p<0.52) whereas; duration of metformin use by the patients had (p<0.01). This is the first report which indicates a significant inverse relationship between blood vitamin B12 level and duration of diabetes among Jordanian patients treated with metformin.